A MARKETING BOOKLET FOR THE ALANA HOTEL SURABAYA: THE BEST WAY TO EMPHASIZE THE UNIQUENESS OF ITS PRODUCTS IN PROMOTING ITSELF TO INSTITUTIONS AND COMPANIES - Lia Margaretha; Jusuf I Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2015)
The Alana is a four-star hotel located in the South of Surabaya. It was built in 2013, which means that it is still a new hotel. Since it is new, it lacks the necessary promotion tool to reach the institutions and companies. In fact, The Alana does not have the promotion tool which emphasizes its excellence and uniqueness of the products. To solve the problem, The Alana needs a marketing booklet, which can help them to show their strengths. This marketing booklet consists of table of contents, company overview (about The Alana), product descriptions (hotel rooms, room types, hotel facilities, and meeting rooms), and contact information (contact us). By having this information, a marketing booklet will become the best tool for The Alana to show the strengths of their products and help them to reach their target market